(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
The study intends to explore the socio-economic vulnerability of climate change in the coastal Koyra Upazila of Bangladesh. The present study is concerned with climate-induced disasters and associated vulnerabilities which adversely impact the social and economic aspects of coastal inhabitants of Bangladesh. The researchers selected four unions (Koyra, Amadi, Bagali, and Dakshin Bedkashi) among the seven unions of Koyra Upazila for this study. In this study, the socio-economic vulnerability of the community people at risk is assessed through the Socio-economic Vulnerability Index (SeVI). This research focused on a mixed-method strategy combining quantitative and qualitative data. By conducting systemic data analysis, the researchers tried to identify the socio-economic vulnerability of the people of selected communities by using the vulnerability index. This study reveals that the study area is highly exposed to climate-induced disasters and extremely sensitive towards the damages caused by these disasters. Moreover, due to the socio-economic vulnerability, the adaptation capacity of the marginalized households remains low. Among sample households, most are affected by the economic vulnerability which limits their capacity to cope with the changing climate and disaster situations. This study not only focuses on the socio-economic vulnerability but also it deals with social perception of the climate-induced disasters of the selected coastal areas of Bangladesh. This index-based assessment with social perception can be an integral part of the contingency planning of the disaster-prone coastal regions of Bangladesh. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(2), 2022, P 67-79